Morphological, Palynological, and Molecular Insights of Arisaema langbiangense: An Endemic Species from Langbiang Plateau, Southern Vietnam (Early view) - Huyen Trang Luu, Hong Quan Bui, Dinh Thach Bui, Hong Truong Luu, Tran Quoc Trung Nguyen, Nga Nguyen-Phi, Thu Trang Le-thi; Hong Thien Van (Tropical Life Sciences Research, 2026)
Arisaema langbiangense is an endemic species first described in Vietnam in 2016, with limited research to date. This study provides the first integrated analysis of its anatomical, palynological, and molecular characteristics to facilitate species identification and future taxonomic work. Anatomically, the leaf, petiole, petiolule, root, and rhizome exhibit distinctive features, including adaxial-abaxial polarity in leaves, homogeneous mesophyll, consistent xylem-phloem orientation, abundant needle-shaped calcium oxalate crystals, and scattered vascular bundles in the rhizome. Pollen grains are large, spheroidal, inaperturate monads with a tectate-echinate exine densely covered in conical spines, consistent with insect-mediated pollination and similar to other Arisaema species. The ITS region (446 bp) of A. langbiangense, newly sequenced and deposited in GenBank, represents the first available ITS region of A. langbiangense for section Anomala. Phylogenetic analysis based on ITS data places the species in a distinct clade, highlighting its genetic uniqueness and supporting sectional relationships consistent with previous plastid-based studies. These findings contribute valuable insights into the taxonomy and evolutionary placement of this poorly known species.